Climate Action Plan for the East and Horn of Africa and Great Lakes Region 2023-2028 - United Nations High Commissioner for Refugees (United Nations, 2023)
As a central component of the 2022-2026 UNHCR Strategic Directions, UNHCR has globally identified eight focus areas that require renewed attention and accelerated effort. One of these is climate action. In 2021, UNHCR published its Strategic Framework for Climate Action and, in 2022, its Operational Strategy for Climate Resilience and Environmental Sustainability (2022-2025).